ANALISIS FRAGMENTASI BATUAN HASIL PELEDAKAN MENGGUNAKAN METODE SCREENING DI GUNUNG REGO KABUPATEN KULONPROGO DAERAH ISTIMEWA YOGYAKARTA - Wanda Suratman; Suratman; Barlian Dwinagara (Retii, 2022)
Scattering of rocks can be done in various ways depending on the characteristics of the rock to be crushed. Blasting activities aim to remove or scatter material from the parent rock so that the size of the resulting fragmentation can facilitate further mining activities. The data used in this study is primary data. blasting geometry needs to modify the spacing because it affects the size of the rock, using a small level of space density will get a smaller rock size and reduce the number of rock boulders or bolder. The results of blasting 1 - 3 are calculated directly after blasting using the screening method with a size of 5 x 5 meters, the rock size is <20 cm = 22.60 percent, 21-40 cm = 25.34 percent, 41-60 cm = 28.08 percent, 61-80 cm = 22.60 percent, and 80 > cm = 1.37 percent. After accumulating the percentage, the size 0-60 = 76.03 percent, 61-80 cm = 23.97 percent, there are still 23.97 percent of rocks whose size is above 60 cm. The size of the retained rock is 61-80 cm = 23.97 percent, because the rock is still above 20 percent, it is necessary to destroy the rock using a mechanical method using a heavy rock breaker.